„Byl to život na sopce, život pod závalem, život v tekoucí lavině”. „Dissident Ghetto” by Pavel Kohout - Kowalska, Urszula (Poznańskie Studia Slawistyczne, 2014)
The main intention of the presented article was to find and indicate thoughts connected to the dissident tradition of Czech 20th century history. The generational experience regarding the „drunken festival” of Prague Spring and brutal intervention of „fraternal help” have influenced a non-official side of Czech modern culture. Literary works, as well as publicist activities in the period 1968–1989 prove that the political opposition has become a very important subject for many writers. In the article, I am referring to above indicated novel written by Pavel Kohout. In his text, the writer, known as one of the most important founding members and architects of the informal civic initiative called Charter 77, has managed to describe an atmosphere of Czech „normalization” and nonofficial ways of rebelling, fighting against the communistic ideology in Czechoslovakia before the Velvet Revolution in November 1989.